“MUSIC OF THE SLAVES” IN THE INDIAN OCEAN CREOLE ISLANDS: A PERSPECTIVE FROM THE SEYCHELLES - Parent, Marie-Christine (International Library of African Music, 2020)
This article examines the development and expression of the moutya from Seychelles, in relation to the sega from Mauritius and the maloya from Reunion.  These musical styles and their associated practices are recognised as evidence of an African heritage in the archipelagos. To better understand their connections and singularities, I utilise a diachronic and synchronic approach, at local and regional levels. The purpose is to demonstrate the mobility of musicians and the permeability of musical practices in these islands over time, using history and narratives from the colonial period (from the end of the seventeenth century) to the present, and fieldwork observations. This approach shows how music and dance elements from Africa are creolised on the islands and how they are further adapted as islanders travel around these islands. In the process one musical practice becomes many, although they fall into a matrix of styles sharing similar features. The article approaches the emergence and the transformation of (what would become) moutya in the Seychelles by first describing the emergence of musical creativity in the Mascarenes and Seychelles. This is followed by a discussion of the transition from a marginal and resistance form of music to new musical categories. Finally, the article describes circulations and musical exchanges between the islands, opening the door to a better understanding of Creole culture and music in the south-western Indian Ocean islands.
Keywords: Creole dialects; Musical Exchange; Sega Dance; Moutya Dance; Mascarenes Islands; Maloya Dance; Seychelles; African Music